2012
DOI: 10.2139/ssrn.1624942
|View full text |Cite
|
Sign up to set email alerts
|

Do Euro Area Countries Respond Asymmetrically to the Common Monetary Policy?

Abstract: We investigate the possible existence of asymmetries among Euro Area countries reactions to the European Central Bank monetary policy. Our analysis is based on a Structural Dynamic Factor model estimated on a large panel of Euro Area quarterly variables. We find that, despite the single monetary policy has had the effect of reducing heterogeneity in impulse responses, member states still react asymmetrically in terms of prices and unemployment, while no difference appears in terms of output. These results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 116 publications
3
9
0
Order By: Relevance
“…28 Moreover, from 27 After the introduction of the fixed rate full allotment tender policy by the ECB in August 2008, the deposit facility can be regarded as the relevant policy rate due to excess reserves, see Beirne (2012) for a very detailed discussion. Consequently, in Figure 1(a) and (b), the policy rate is depicted by the main refinancing operations (MRO) up to August 2008 and the deposit facility (DF) afterward.…”
mentioning
confidence: 99%
“…28 Moreover, from 27 After the introduction of the fixed rate full allotment tender policy by the ECB in August 2008, the deposit facility can be regarded as the relevant policy rate due to excess reserves, see Beirne (2012) for a very detailed discussion. Consequently, in Figure 1(a) and (b), the policy rate is depicted by the main refinancing operations (MRO) up to August 2008 and the deposit facility (DF) afterward.…”
mentioning
confidence: 99%
“…Accordingly, they found that monetary policy shocks might cause an increase in employment under alternative specifications. Barigozzi et al (2014) employed a structural dynamic factor model estimated on a large panel of euro area quarterly variables, emphasizing that the reactions to the European Central Bank monetary policy might differ between North and South Europe in terms of prices and unemployment due to the country-specific structures. Similar results were also obtained by Perry et al (2015), who found that the differences in the responses of real wages to monetary policy shocks might arise from cross-state differences in unemployment, the share of agriculture in the state GDP, the unionization rate and the importance of intermediate goods in state production by estimating structural vector autoregression (SVAR) models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Economists have been attracted by these models because they allow to analyze large panels of time series without suffering of the curse of dimensionality. Furthermore, these models proved successful in forecasting (Stock and Watson, 2002a,b;Forni et al, 2005;Giannone et al, 2008;Luciani, 2014), in the construction of both business cycle indicators and inflation indexes (Cristadoro et al, 2005;Altissimo et al, 2010), and also in policy analysis based on impulse response functions (Giannone et al, 2005;Stock and Watson, 2005;Forni et al, 2009;Forni and Gambetti, 2010;Barigozzi et al, 2014;Luciani, 2015), thus becoming a standard econometric tool in empirical macroeconomic analysis.…”
Section: Introductionmentioning
confidence: 99%